BEYOND DECODING: INVESTIGATING THE IMPACT OF CRITICAL LITERACY APPROACH ON EFL LEARNERS’ READING SKILLS - Fentry Hernaningsi Ruing; Baso Jabu; Sultan Baa (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates the impact of the Critical Literacy Approach (CLA) on the development of critical reading skills among EFL university students. The study was motivated by the persistent challenge that many reading classrooms in Indonesia remain focused on surface-level comprehension rather than fostering critical engagement with texts. Employing a qualitative case study design, this study involved 15 undergraduate students from three different universities in Makassar, Indonesia. Data were collected through classroom observations and semi-structured interviews, then analyzed using thematic coding. Findings revealed that the implementation of CLA fostered students' critical reading achievement across six core domains: textual analysis, evaluation, contextual awareness, critical response, reflective insight, and intertextual thinking. Students demonstrated improved abilities to identify arguments, reflect on moral values, and make intertextual and real-world connections. However, variation in engagement levels indicates that some students still lack confidence and critical voice, particularly in articulating reasoned responses or understanding socio-political contexts. These findings suggest that while CLA has strong potential to deepen comprehension and promote transformative learning, its success depends on consistent pedagogical support, dialogic instruction, and contextually relevant content. The study is limited by its scope, focusing only on a small sample from Makassar. Further research is needed across diverse regions in Indonesia to generalize the findings and enhance the development of critical literacy nationwide. This study contributes to the field by offering an empirically grounded, student-centered framework for evaluating critical reading growth, highlighting the practical value of CLA in EFL contexts.